Regional integration and trade costs in South Asia - Nilanjan Banik; John Gilbert (Asian Development Bank Institute (ADBI), 2008)
Until now, the value of inter-country trade within South Asian nations has been low. While similarities in the exports profiles can be seen as a reason for this low value of trade, it might not be a valid one, especially given the presence of growing South Asian income. The intraindustry trade theory suggests that complementarity might actually increase trade in the presence of a rising income. There may be other important factors such as trade costs. Using an augmented gravity model in a panel framework, we try to identify the components of trade costs that might have resulted in lower inter-country South Asian trade.
Keywords: C32; F02; F15; 330